Global competition : law, markets and globalization - Gerber, David J. (Oxford : Oxford University Press, 2010)
A key factor in the emerging relationship between law and economic globalization is how global competition now shapes economies and societies. Competition law is provided by those players that have sufficient 'power' to apply their laws transnationally. This text examines this controversial aspect of globalization.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Antitrust law (International law)